Feasibility of an online platform delivery of pulmonary rehabilitation for individuals with chronic respiratory disease. Issue 1 (24th March 2021) - Lewis, Adam; Knight, Ellena; Bland, Matthew; Middleton, Jack; Mitchell, Esther; McCrum, Kate; Conway, Joy; Bevan-Smith, Elaine
Abstract : Introduction: SARS-CoV-2 has restricted access to face-to-face delivery of pulmonary rehabilitation (PR). Evidence suggests that telehealth-PR is non-inferior to outpatient PR. However, it is unknown whether patients who have been referred to face-to-face programmes can feasibly complete an online-PR programme. Methods: This service evaluation used a mixed-methods approach to investigate a rapid PR service remodelling using the University of Gloucestershire eLearn Moodle platform. Quantitative baseline demographic and PR outcome data were collected from online-PR participants, and semistructured interviews were completed with PR staff and participants. Results: Twenty-five individuals were eligible from a PR waiting list. Thirteen declined participation and 14 completed PR. Significant pre-post online PR improvements were achieved in 1 min sit-to-stand (CI 2.1 to 9 (p=0.004)), Generalised Anxiety Disorder (CI −0.3 to −2.6 (p=0.023)), Primary Health Questionnaire-9 (CI −0.3 to −5.1 (p=0.029)), Chronic Respiratory Questionnaire dyspnoea (CI 0.5 to 1.3 (p=0.001)), fatigue (CI 0.7 to 2 (p=0.0004)), emotion (CI 0.7 to 1.7 (p=0.0002)), mastery (CI 0.4 to 1.3 (p=0.001)). Interviews indicated that patient PR inclusion was made possible with digital support and a PR introduction session improved participant engagement and safety. Incremental progression of exercise was perceived as more successful online compared with face-to-face PR. However, perceptions were that education sessions were less successful. Online-PR required significant staff time resource. Discussion: Online-PR improves patient outcomes and is feasible and acceptable for individuals referred for face-to-face PR in the context of a requirement for social distancing. Face-to-face programmes can be adapted in a rapid fashion with both staff and participants perceiving benefit. Future pragmatic trials are now warranted comparing online-PR including remote assessments to centre-based PR with suitably matched outcomes, and patient and staff perceptions sought regarding barriers and facilitators of online delivery.